AudioInSpace: Exploring the Creative Fusion of Generative Audio, Visuals and Gameplay - Hoover, Amy K.; Cachia, William; Liapis, Antonios; Yannakakis, Georgios N. (Evolutionary and Biologically Inspired Music, Sound, Art and Design, 2015)
Computer games are unique creativity domains in that they elegantly fuse several facets of creative work including visuals, narrative, music, architecture and design. While the exploration of possibilities across facets of creativity offers a more realistic approach to the game design process, most existing autonomous (or semi-autonomous) game content generators focus on the mere generation of single domains (creativity facets) in games. Motivated by the sparse literature on multifaceted game content generation, this paper introduces a multifaceted procedural content generation (PCG) approach that is based on the interactive evolution of multiple artificial neural networks that orchestrate the generation of visuals, audio and gameplay. The approach is evaluated on a spaceship shooter game. The generated artifacts — a fusion of audiovisual and gameplay elements — showcase the capacity of multifaceted PCG and its evident potential for computational game creativity.